“Smouldering conditions of the shoulder” Lest we forget! - Anupam Wakhlu; Archana Wakhlu; Vini Tandon; Narendra Krishnani (Indian Journal of Rheumatology)
The shoulder joint may be involved in seronegative spondyloarthropathy, calcium pyrophosphate dihydrate disease and degenerative joint disease. Adhesive capsulitis, calcific tendonitis and rotator cuff degeneration are other diseases that can involve the shoulder. The shoulder joint area may be involved as a consequence of extra-articular disease, and massive shoulder swelling may rarely result. Herein, five uncommon diseases presenting with predominant large shoulder swelling are described. The typical clinical and radiological findings with diagnostic features are highlighted.